OPTIMIZATION OF CUSTOMER LOYALTY AT COFFEE SHOPS IN SURABAYA - Rinawati, Liya; Harno, Rinto; Hasibuan, Putri Septi Naulina (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The main key to winning in competition for companies is to provide value and satisfaction to consumers through the delivery of quality products and services. This can be achieved by providing products and services that are more satisfying than those of competitors, resulting in satisfied consumers, consistent service quality, and consumer loyalty. This research aims to analyze sales optimization strategies by increasing service quality and customer loyalty of coffee shops in Surabaya, using a causal research design with quantitative methods. Data was collected through questionnaires distributed to people in Surabaya who had visited and bought from coffee shops. The data analysis technique used was Structural Equation Modeling analysis with Partial Least Square. Results showed that store location and store image had a significant positive effect on service quality, and store location, store image, and service quality had a significant positive effect on customer loyalty. The recommended strategies include improving store location by making signs that are easy to reach, and improving store image through endorsements and other promotions to attract customer attention.